Ellis and Kent: Disability and the Media, 4-Vol. Set - Ellis, K.; Kent, Michael (Routledge, 2017)
Now, this new four-volume collection from Routledge's acclaimed Critical Concepts in Media and Cultural Studies series enables users readily to access and make sense of the essential texts of disability-and-media scholarship.